Minimizing Energy Consumption on Mobile Phone by Rearranging Transport Protocol Load - Suherman, S; Mubarakah, Naemah; Al-Akaidi, Marwan (International Journal of Engineering and Technology, 2018)
There are two transport layer protocols that have been used in the internet protocol (IP) networks: Transmission Control Protocol (TCP) and User Datagram Protocol (UDP). Both protocols have been utilized for video streaming applications. This paper examines energy consumed by a mobile device when TCP or UDP employed by the application within it for streaming a video file. A transport protocol load management is proposed to reduce the mobile device energy consumptions. The experiments were conducted in the 802.11 environment. The results show that the proposed method is able to minimize mobile device energy consumptions up to 10.7% and 3.34% for both TCP and UDP protocols. Â Â